Simulasi Numerik Kurva Hubungan Momen Dan Kurvatur Balok Beton Bertulang Dengan Variasi Penampang - Heru Setiadi; Zulfikar Djauhari; Reni Suryanita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Beam as one of structural elements is generally designed to exhibit ductile behavior before failure. The ductility of the whole structure is affected by the characteristic of its structural elements. The ductility of reinforced concrete (RC) beam could be measured by curvature ductility parameter. Curvature ductility is defined as the ratio between the beam curvature at ultimate state and yielding state. The ductility curvature value can be calculated based on the moment-curvature curve. One of the structural analysis softwares that can be used to produce the moment-curvature relationship curve is Response2000. This research aims to analyze the impact of varying the reinforced concrete beam characteristics to the ductility of the beam which is performed using Response2000 software to model the singly-reinforced concrete beam. By varying the concrete compressive strength, reinforcing bar (rebar) strength and diameter, reinforcement ratio, and concrete section (width and depth of concrete), 38 models of beam were generated. Based on the analysis results, it was observed that the increment of concrete compressive strength and effective depth increases curvature ductility, whereas the increment of rebar strength and reinforcing ratio reduces curvature ductility. Manual calculations on the curvature ductility showed that the output produced by Response2000 only the average difference from the manual calculations is 15,361%. This indicates that Response2000 is a reliable tool to calculate the curvature ductility of reinforced concrete beam.Keywords: ductility, reinforced concrete, moment, curvature, Response2000